Assessing the Environmental Impact of Compostable Bioplastic BagsTapsi Jain, Yashika Grover, Shreya Jain, Hyma Yadav - Jain, Tapsi; Grover, Yashika; Jain, Shreya; Yadav, Hyma (International Journal of Environment, Agriculture and Biotechnology, 2024)
Plastics made from fossil fuels contribute to pollution and disrupt ecosystems. While bioplastics and compostable bags that are made from renewable materials offer promising alternatives, they can also have severe effects such as eutrophication. Bioplastics can increase the soil nutrients like nitrogen (under certain conditions). A huge impact has been made by bioplastic additives on soil’s physical, chemical, and biological properties, land, human health, flora and fauna, and the environment in general.